Comparing the impact of microplastics derived from a biodegradable and a conventional plastic mulch on plant performance - Zantis, Laura J.; Adamczyk, Sylwia; Velmala, Sannakajsa M.; Adamczyk, Bartosz; Vijver, Martina G.; Peijnenburg, Willie; Bosker, Thijs (Elsevier, 2024)
Agricultural lands have been identified as plastic sinks. One source is plastic mulches, which are a source of micro- and nano-sized plastics in agricultural soils. Because of their persistence, there is now a push towards developing biodegradable plastics, which are designed to undergo (partial) breakdown after entering the environment. Yet, limited research has investigated the impacts of both conventional and biodegradable plastics on distinct plants. Moreover, comparisons among studies are difficult due to differences in experimental design. This study directly compares the effects of artificially weathered conventional polyethylene (PE) and starch-based biodegradable polybutylene adipate terephthalate (PBAT) on four food crops, including two monocots (barley, Hordeum vulgare, and wheat, Triticum aestivum L.) and two dicots (carrot, Daucus carota, and lettuce, Lactuca sativa L.). We investigated the effects of environmentally relevant low, medium, and high (0.01 %, 0.1 %, 1 % w/w) concentrations of PE and starch-PBAT blend on seed germination (acute toxicity), and subsequently on plant growth and chlorophyll through a pot-plant experiment (chronic toxicity). Germination of all species was not affected by both plastics. However, root length was reduced for lettuce and wheat seedlings. No other effects were recorded on monocots. We observed a reduction in shoot length and bud wet weight of carrot seedlings for the highest concentration of PE and starch-PBAT blend. Chronic exposure resulted in a significant decrease in shoot biomass of barley and lettuce. Additionally, a positive increase in the number of leaves of lettuce was observed for both plastics. Chlorophyll content was increased in lettuce when exposed to PE and starch-PBAT blend. Overall, adverse effects in dicots were more abundant than in monocots. Importantly, we found that the biodegradable plastic caused more commonly adverse effects on plants compared to conventional plastic, which was confirmed by a mini-review of studies directly comparing the impact of conventional and biodegradable microplastics.
Keywords: mikromuovi; itäminen; kasvien kasvu; myrkyllisyys; maatalous; biohajoaminen; microplastic; biodegradable plastic; toxicity; agriculture; seed germination; plant growth